VIABILITY OF DUAL-SPECIES BIOFILM OF STREPTOCOCCUS MUTANS AND LACTOBACILLUS ACIDOPHILUS AFTER APPLICATION OF MAULI BANANA STEM GEL - Amy Nindia Carabelly; Dhya Aurellia Salsabila Karno; Isyana Erlita; Aninditya Pimas Trianuanty (FKG Unlam, 2022)
Introduction: Dual-species biofilm of Streptococcus mutans and Lactobacillus acidophilus in dental caries has a higher viability or ability to survive in comparison to mono-species biofilm, consequently it is more resistant to antibiofilm. Mauli banana stem gel (MBSG) contains isoleucine, cinnamic acid, and another bioactive constituents that may work as antibiofilm, hence it is able to decrease the viability of dual-species biofilm of S. mutans and L. acidophilus. This research aims to analyze the effect of MBSG on viability of dual-species biofilm of S. mutans and L. acidophilus. Material and methods: This research is a true experimental research with post test only with control group design which divides dual-species biofilm of S. mutans and L. acidophilus into 12 groups with 4 replications. Group 1 are given 0.2% chlorhexidine gel (positive control), group 2 are not given any treatment (negative control), group 3 are the media control, and group 4-12 are given MBSG concentration of 6.25%, 12.5%, 25%, 37.5%, 50%, 62.5%, 75%, 87.5%, and 98%. Each group is incubated for 72 hours, afterward is given MTT reagent and read using a microplate reader. Results: The result of Kruskal-Wallis (p=0,00) and Mann-Whitney test showed significant difference between all treatment groups and control groups. Conclusion: MBSG concentration of 6.25%, 12.5%, 25%, 37.5%, 50%, 62.5%, 75%, 87.5%, and 98% are able to decrease the viability of dual-spesies biofilm of S. mutans and L. acidophilus.